2012
DOI: 10.1080/00103624.2012.639427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Fertilizers on Cotton Yield and Nitrogen Uptake Efficiency in an Aridisol

Abstract: A field experiment was carried out to study the effect of different rates of potassium (K) fertilizer [0, 50, 100, and 150 potassium oxide (K 2 O) ha -1 ] in the presence of increased supply of nitrogen (N) (120, 180, and 240 kg N ha -1 ) on cotton (Gossypium hirsutum L.) yield and the N and K use efficiencies using the 15 N isotopic dilution technique. Potassium fertilizer increased cotton yield, which was significant and more pronounced with the application of N in the high level (N3). The greatest cotton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Maximum fertilizer gives maximum plant growth as compared to minimum does rates of nitrogen. Similar results of fertilizers effect on plant growth were defined by Khalifa et al (2012) that frequently application of nitrogen fertilizers in the field will improve the plant ability to high uptake of nitrogen. Nitrogen application can be effective if it is applied on time when the plant demand is high (Setatou and Simonis 1995).…”
Section: Discussionsupporting
confidence: 61%
“…Maximum fertilizer gives maximum plant growth as compared to minimum does rates of nitrogen. Similar results of fertilizers effect on plant growth were defined by Khalifa et al (2012) that frequently application of nitrogen fertilizers in the field will improve the plant ability to high uptake of nitrogen. Nitrogen application can be effective if it is applied on time when the plant demand is high (Setatou and Simonis 1995).…”
Section: Discussionsupporting
confidence: 61%
“…Another consideration that affects K dynamics is agronomic practices which may include past planting history and management of soil, coupled with the thermal and moisture conditions (Yang et al, 2016). Increased lint yield response to K treatment over the control has been reported by others (Mullins et al, 1999;Gormus, 2002;Pettigrew, 2003;Coker et al, 2009;Khalifa et al, 2012;Zia-ul-hassan et al, 2014;Yang et al, 2016). However, the inconsistent results from the effect of the split and single season applications makes it difficult to conclude on the best method of application within the region unlike what others have reported (Joshi and Rudraradhya, 1999;Gormus, 2002;Gormus and Yucel, 2002;Yang et al, 2016).…”
Section: Cotton Lint Yieldmentioning
confidence: 93%
“…Field studies revealed significant increases in plant growth due to an increase in the Ca:NH 4 ratio. In addition, previous research has also reported a positive influence of potassium on N uptake (Khalifa et al 2012). An ample supply of potassium to plant roots counteracts a possible toxic effect of ammonium nutrition, enhancing ammonium utilization.…”
Section: Introductionmentioning
confidence: 91%
“…Authors such as Santa-Maria et al (2000) have reported a protective role of adequate K+ concentration against the detrimental effects of high NH +4 concentrations. Other authors such as Khalifa et al (2012) have also suggested that K+ in plant roots could counteract a possible toxic effect of ammonium nutrition, enhancing ammonium utilization. It is concluded that K+ may alleviate NH +4 toxicity, partly by inhibiting NH +4 uptake, partly by stimulating N assimilation in the roots, and decreasing its volatilization.…”
Section: Use Of Nitrogen and Maize Grain Yieldmentioning
confidence: 99%